CFD Simulation of Various Two-Phase Flow Patterns in Y-Shaped Microfluidic Channels - Younes Amini; Valiyollah Ghazanfari; Amir Hossein Saeedi Dehaghani; Mohammad Mahdi Shadman; Fatemeh Mansourzadeh (Journal of Chemical and Petroleum Engineering)
This study presents a computational fluid dynamics (CFD) simulation of two-phase flow patterns in a Y-shaped microfluidic device. The two-phase flow of water and n-butyl acetate is simulated using the volume of fluid (VOF) method in a Y-shaped microfluidic device with different flow rates. A 2D model was used for simulation, and the results were compared to experimental data, showing good consistency. The study also examined the effects of organic (n-butyl acetate) and flow on the overall flow model. The authors observe three different flow patterns, including slug flow, parallel flow, and droplet flow, depending on the flow rate. The results indicate that a slug flow pattern is detected when the flow rates of the aqueous and organic phases are both low and similar. Nonetheless, as the overall flow rate rises, the slug flow pattern shifts to either parallel droplet or plug flow. Similarly, when the flow rate of the aqueous phase is increased while keeping the organic phase flow rate constant, the shift occurs from slug flow to droplet flow. Therefore, this study is significant in providing insights into the different flow regimes that can occur in a microfluidic system. This understanding can be used to design and optimize microfluidic devices for a variety of applications.